Les genres récrits n° 1 - Daniel Elmiger (Glad!)
Today, the awareness that a text shouldn’t be written without gender-bias is steadily growing – yet it is not always clear what this means and which strategies are best suited to achieve that goal. In certain texts, a footnote makes an explicit statement about forms or constructions that are used, e. g. generically used masculine forms. This column explores the meaning and the utility of such footnotes.